Changes between Initial Version and Version 1 of Ticket #26105, comment 10
 Timestamp:
 08/29/18 11:47:59 (3 years ago)
Legend:
 Unmodified
 Added
 Removed
 Modified

Ticket #26105, comment 10
initial v1 1 1 Sorry, my question was how to do this in Sage precisely. So, I can map `k(α)→k[x]` by mapping the generator to `x`. Then I map `k[x]→l[x]` by using an induced map. Finally I use the evaluation `l[x]→l`. But are people really supposed to figure this out on their own? 2 2 3 If I understand your proposal in comment 7 above, you would like to see a shortcut to define `k[x]→l` as `(k[x]).hom(α', base_morphism=k→l)`. But why don't go all the way and allow people to write `(k(α)).hom(α', base_morphism=k→l)`?3 If I understand your proposal in comment 7 above, you would like to see a shortcut to define `k[x]→l` as `(k[x]).hom(α', base_morphism=k→l)`. But why not go all the way and allow people to write `(k(α)).hom(α', base_morphism=k→l)`?